Performance based energy, ecological and financial costs of a sustainable alternative cement. (10th March 2021) - Kulasuriya, Chandana; Vimonsatit, Vanissorn; Dias, W.P.S.
Abstract: This paper presents a comparison of the energy and ecological impacts and financial costs of Alkali Pozzolan Cement (APC), High Volume Fly Ash (HVFA) cement and Ordinary Portland Cement (OPC) mixtures. The embodied energy, carbon dioxide emission and financial costs were calculated per unit weight of dry binder powder; per unit volume per unit strength of hydrated hardened binder; and finally per unit volume per unit strength per year of service. The performance based indicators therefore consider both strength and durability; with the latter based both on carbonation and chloride environments. The statistical means and variability of the costs were also computed. The results indicate that the energy, ecological and financial costs of APC are very attractive compared to those of OPC or HVFA, when considered either as the cost per unit weight of binder or as the cost per unit performance, whether related to unit strength or both unit strength and year of service. The variability of the APC cost indicators was also the lowest in general among the cements considered. However, OPC is still arguably the best when only carbonation exposure is involved during service. Highlights: Energy, carbon and financial costs are found for OPC, HVFA and Alkali Pozzolan Cement. The above costs are calculated per unit volume and strength and year of service. Service life under carbonation and chloride ingress were found using durability data. The alkali pozzolan cement had very low costs and also relatively low variability. Carbonation and chloride exposures produced inverse orderings of cement costs.